Azole Fungicides and Their Endocrine Disrupting Properties: Perspectives on Sex Hormone-Dependent Reproductive Development - Draskau, Monica Kam; Svingen, Terje (Frontiers in Toxicology, 2022)
Azoles are antifungal agents used in both agriculture and medicine. They typically target the CYP51 enzyme in fungi and, by so doing, disrupt cell membrane integrity. However, azoles can also target various CYP enzymes in mammals, including humans, which can disrupt hormone synthesis and signaling. For instance, several azoles can inhibit enzymes of the steroidogenic pathway and disrupt steroid hormone biosynthesis. This is of particular concern during pregnancy, since sex hormones are integral to reproductive development. In other words, exposure to azole fungicides during fetal life can potentially lead to reproductive disease in the offspring. In addition, some azoles can act as androgen receptor antagonists, which can further add to the disrupting potential following exposure. When used as pharmaceuticals, systemic concentrations of the azole compounds can become significant as combatting fungal infections can be very challenging and require prolonged exposure to high doses. Although most medicinal azoles are tightly regulated and used as prescription drugs after consultations with medical professionals, some are sold as over-the-counter drugs. In this review, we discuss various azole fungicides known to disrupt steroid sex hormone biosynthesis or action with a focus on what potential consequences exposure during pregnancy can have on the life-long reproductive health of the offspring.